The ethics of indeterminacy in the novels of William Gaddis - Comnes, Gregory (University Press of Florida, 1994)
William Gaddis is one of the most significant postwar American novelists. His three large and experimental works - The Recognitions, J R (which won the National Book Award in 1975), and Carpenter's Gothic - sell to a reverential underground. In this first discussion of the ethical dimension of Gaddis's novels, Gregory Comnes maintains that Gaddis writes "epistemological" novels, narratives whose form provides readers with the means to understand how a postmodern ethics is possible